Content-Centric Networks An Overview, Applications and Research Challenges - Ahmed, Syed Hassan; Bouk, Safdar Hussain; Kim, Dongkyun (SpringerBriefs in Electrical and Computer Engineering,, 2016)
This book introduces Content-Centric Networking (CCN), a networking paradigm that provides a simple and effective solution to the challenging demands of future wired and wireless communications. It provides an overview of the recent developments in the area of future internet technologies, bringing together the advancements that have been made in Information-Centric Networking (ICN) in general, with a focus on CCN. It begins with an introduction to the basics of CCN is followed by an overview of the current internet paradigm and its challenges. Next, an application perspective has been included, where the authors encompass the selected applications for CCN with recent refereed research and developments. These applications include Internet of Things (IoT), Smart Grid, Vehicular Ad hoc Networks (VANETs), and Wireless Sensor Networks (WSNs). The book is a useful reference source for practising researchers, and can be used as supporting material for undergraduate and graduate level courses in computer science and electrical engineering.